Tindak Tutur Ilokusi Ekspresif dalam Film " Ketika Berhenti di Sini" - Hurint, Elisabeth; Djuli , Labu; Pekuwali, Dian Sari A. (Jurnal Lazuardi, 2025)
This research focuses on the form of expressive illocutionary speech acts in the movie “When It Stops Here”. The purpose of this research is to analyze the expressive illocutionary speech acts in the film “When It Stops Here”. The method used in this research is descriptive qualitative. This method is used to analyze information related to expressive illocutionary speech acts in the film “When It Stops Here”. The data collection technique in this research uses listening technique or SLBC in which the researcher listens to the use of language without participating in the conversation process. This research refers to the theory of pragmatics. The result of this research shows that there are 22 expressive illocutionary speech acts, namely (1) speech acts of congratulation there are 4 utterances, (2) speech acts of thanks there are 5 utterances, (3) speech acts of apologizing there are 6 utterances (4) speech acts of praising there are 3 utterances, (5) speech acts of criticizing there are 1 utterance, (7) speech acts of insinuating there are 1 utterance, (8) speech acts of condoling there are 1 utterance.